Notes on the Spatial Turn - Grgas-Mufa, Stipe (Array, 2012)
The article takes issue with Soja's contention that the spatial turn was an answer to the "ontological distortion" by which time became the focus of interest in the 19th century. On the contrary the author mainatains that what occured was a different positioning of disciplines and describes the consequences of this assessment.